Effect of stocking densities on growth, production and survival rate of red tilapia in hapa at fish hatchery Chilya Thatta, Sindh, Pakistan - Daudpota, Abdul Malik; Kalhoro, Illahi Bux; Shah, Sajjad Ali; Kalhoro, Hameeda; Abbas, Ghulam (Journal of Fisheries, 2014)
Effect of stocking density on growth, production and survival of red tilapia (Oreochromis mossambicus × O. niloticus) were conducted in hapa for 60 days at Chilya Thatta. Tilapia fry (4.5±0.02 cm, 2.0±0.01 g) were stocked into hapa (4.5x2.4x1 m). Three treatments with two replicates were used: T1-200; T2-250 and T3-300 fry/hapa. Fry were fed twice a daily with pelleted feed containing 35% protein, 5% of total biomass. After 60 days, the highest growth were determined in T1 (49.8±0.0 g) while in T3 lowest growth (29.09±0.0 g) was recorded. Production (9.56, 10.13 and 8.12 kg/m3/60days) in T1, T2 and T3 respectively were significantly different (P<0.05) to each other. Feed conversion ratio of 0.48, 0.48 and 0.49 in T1, T2 and T3, respectively not significantly different (P>0.05). Survival was significantly different among treatments (P<0.01). Highest survival (100%) was attained in T1 with lower stocking density, followed by T2 (98%) and T3 (95%). Water quality parameters recorded throughout the study period were found within the ranges for fish culture such as temperature 27.2 to 28.5 °C, dissolved oxygen 5.8 to 6.4 mg/l, pH 6.9 to 7.6, ammonia from 0.45 to 0.51 mg/l, hardness 106 to 110 ppm and nitrite 0.151 to 0.162 mg/l.